Crew-Friendly Countermeasures Against Musculoskeletal Injuries in Aviation and Spaceflight - O’Conor, Daniel K.; Dalal, Sawan; Ramachandran, Vignesh; Shivers, Bethany; Shender, Barry S.; Jones, Jeffrey A. (Frontiers in Physiology, 2020)
Aviation and space medicine face many common musculoskeletal challenges that manifest in crew of rotary-wing aircraft (RWA), high-performance jet aircraft (HPJA), and spacecraft. Furthermore, many astronauts are former pilots of RWA or HPJA. Flight crew are exposed to recurrent musculoskeletal risk relating to the extreme environments in which they operate, including high-gravitational force equivalents (g-forces), altered gravitational vectors, vibratory loading, and interaction with equipment. Several countermeasures have been implemented or are currently under development to reduce the magnitude and frequency of these injuries. Cervical and lumbar spine, as well as extremity injuries, are common to aviators and astronauts, and occur in training and operational environments. Stress on the spinal column secondary to gravitational loading and unloading, +/- vibration are implicated in the development of pain syndromes and intervertebral disk pathology. While necessary for operation in extreme environments, crew-support equipment can contribute to musculoskeletal strain or trauma. Crew-focused injury prevention measures such as stretching, exercise, and conditioning programs have demonstrated the potential to prevent pre-flight, in-flight, and post-flight injuries. Equipment countermeasures, especially those addressing helmet mass and center of gravity and spacesuit ergonomics, are also key in injury prevention. Furthermore, behavioral and training interventions are required to ensure that crew are prepared to safely operate when faced with these exposures. The common operational exposures and risk factors between RWA and HPJA pilots and astronauts lend themselves to collaborative studies to develop and improve countermeasures. Countermeasures require time and resources, and careful consideration is warranted to ensure that crew have access to equipment and expertise necessary to implement them. Further investigation is required to demonstrate long-term success of these interventions and inform flight surgeon decision-making about individualized treatment. Lessons learned from each population must be applied to the others to mitigate adverse effects on crew health and well-being and mission readiness.